Emotional Intelligence and Work Engagement in Working Mother - Sowanya Ardi Prahara; Astuti Wulandari (Journal of Psychology and Instruction, 2022)
Career women often face obstacles due to their roles as workers and as housewives. This is caused by the negative cognitions and emotions experienced by married women which can lead to a decrease in the level of work engagement. Meanwhile, to be fully involved in individual work requires self-utilization, both cognitively and emotionally. This study aims to analyze the relationship between emotional intelligence and work engagement in married career women. Subjects in this study amounted to 70 people who have the characteristics of a career woman who is married, with a minimum of one year of work. Subjects were taken using purposive sampling method. Collecting data in this study using the Emotional Intelligence Scale and Work Engagement Scale. The data analysis technique used is the product moment correlation of Karl Pearson. Based on the results of data analysis obtained a correlation coefficient (R) of 0.479 with p = 0.000 (p <, 0.05). These results indicate that there is a positive relationship between emotional intelligence and work engagement.  To maintain and improve emotional intelligence can be done with meditation, doing fun activities, and reflection to practice the ability to understand yourself and others.